New classification of value institutionalization mechanisms - Neda Mohammad Esmaeili; Ashkan Khalili; Aryan Gholipour (Cogent Business & Management, 2020)
The history of organizational values illustrates that after firms understand the importance of values to reach their goals while remaining legitimate, they define certain values based on institutional isomorphism. Unfortunately, for most firms, these values are only on paper, rather than being practiced in employees' daily behavior. Therefore, another wave of research to institutionalize values has taken root in organizations. In this study, an action research is used in order to identify appropriate institutional mechanisms, and the research was conducted on a company with six approved organizational values. As a result of performing multiple interviews, organizing several focus groups, and distributing questionnaires, institutional mechanisms were identified along with the necessary action plan to implement them. Accordingly, after a two-year period, the level of institutional values was evaluated and certain suggestions were made. This research represents a new categorization of institutionalization mechanisms using organizational culture literature and models of institutionalization.
Keywords: 650; organizational culture; organizational value; institutionalization mechanism